Estimation of Dengue Fever Transmission Model in West Java Using the Ensemble Kalman Filter Method - Addinda Nur Ameliyah; Didik Khusnul Arif (Universitas Islam Lamongan, 2026)
Dengue Fever Transmission is a serious, potentially fatal infectious if unmanaged disease. It caused by the dengue virus, transmitted by Aedes aegypti and Aedes albopictus mosquitoes. In West Java, cases remain high and fluctuate significantly, requiring precise mathematical modeling to describe transmission dynamics. This is the first study applying Ensemble Kalman Filter (EnKF) in West Java to estimate the SEIR-SI model, compared to Unscented Kalman Filter (UKF), using dengue fever transmission case data from 2010–2023. Performance was assessed via Mean Absolute Percentage Error (MAPE) for the infected human population ( ), showing EnKF’s superior accuracy (2.4%) over UKF (7.8%). EnKF effectively estimates hard-to-measure epidemiological variables and this study can support government prediction-based dengue fever transmission control policies.